Harnessing Community-Based Aquaculture for the Sustainable Development of Small Scale Fishery - Pamesa, Danielle; Ferolin, Ma. Cecilia; Sison, Maria Pia; Suson, Peter; Porras, Marph Daryl (Journal of Interdisciplinary Perspectives, 2025)
This study examines how the principles of sustainable development can be realistically applied to community-based aquaculture in small-scale fisheries. Using the case of the Simbuco Aqua-Marine Multi- Purpose Cooperative (SAMMPC) in Kolambugan, Lanao del Norte, this research explores the socio- economic and ecological dimensions of aquaculture activities and their broader implications for sustainability in small-scale fisheries. The study is framed within key Sustainable Development Goals (SDGs), particularly SDG 14 (Life Below Water) and SDG 8 (Decent Work and Economic Growth), highlighting how SAMMPC’s initiatives align with global sustainability efforts. A mixed-methods approach was employed, integrating quantitative surveys with qualitative key informant interviews (KII) and focus group discussions (FGD). Findings indicate that SAMMPC has significantly improved members’ livelihoods through diversified income streams, enhanced credit access, and strengthened social cohesion. Notably, the cooperative fosters inclusivity by promoting women’s participation in aquaculture, contributing to SDG 5 (Gender Equality). However, challenges such as environmental degradation, resource depletion, and market instability highlight the complexities of balancing economic growth with ecological sustainability. While SAMMPC serves as a model for cooperative-based aquaculture, the study underscores the broader need for sustainable practices across small-scale fisheries. The research advocates for biodiversity-friendly aquaculture methods, climate-adaptive strategies, and improved waste management systems to mitigate environmental risks. By integrating these approaches and fostering multi-stakeholder partnerships, community-based aquaculture can be a viable pathway for sustainable development, ensuring both economic viability and ecological resilience.